Contribution Hand-Eye Coordination And Balance To Petanque Shooting Ability In Sports Education Students At Muhammadiyah University Of Surakarta - Riandika Permadi; Nurhidayat (International Journal of Educational Research & Social Sciences, 2021)
Hand-eye coordination is a factor of physical condition that greatly affects the concentration in determining the direction of accuracy in a movement performed. Balance is the ability that each individual has to control the concentration of the brain in a movement that involves reaction action over each change in body position to be stable to get maximum accuracy.  In sports talent, petanque Muhammadiyah University of Surakarta students have never been tested regarding hand-eye coordination for the accuracy of shooting movements. This research aims to determine whether or not there is a contribution of hand-eye coordination and balance to petanque shooting skills in student sports education at the Muhammadiyah University of Surakarta. In the method, this research uses a quantitative method with a correlational approach. The sample in this study was a sports education student who joined the sports talent petanque Muhammadiyah University of Surakarta as many as 15 students. This research uses the population of students, especially sports talent petanque Muhammadiyah University of Surakarta male students who number 15 students. The process of sampling used in this study is a sampling technique aimed at (purposive sampling) researchers set certain conditions. The result of data processing obtained from hand-eye coordination and balance to petanque shooting ability in 15 UMS sports education students amounted to 28.8%. The regression coefficient of the two variables against petanque shooting capability is 0.288. With the significance of multiple regressions known F_count = 5,423 smaller than the F_teble(2:12)  = 3.88 at the α = 0.05. From the above results, it can be concluded that the decision H1 was accepted and H0 rejected. Therefore, it can be concluded that there is a contribution of hand-eye coordination to petanque shooting capabilities in At student sports the education Muhammadiyah University of Surakarta.